AGE CHARACTERISTICS OF MELATONIN 1A RECEPTORS’ DENSITY IN NEURONS OF THE ANTERIO-LATERAL PREOPTIC NUCLEUS OF RATS’ HYPOTHALAMUS UNDER LIGHT STIMULATION AND ADMINISTRATION OF MELATONIN - Bulyk, R.Ye.; Yosypenko, V.R.; Yosypenko, Yu.R.; Proniaiev, D.V.; Vlasova, K.V.; Voloshyn, V.L.; Smetaniuk, O.V. (World of Medicine and Biology, 2023)
The article provides a comparative analysis of the results of an immunohistochemical study of the melatonin type 1A receptors’ density in the neurons of the anterolateral preoptic nucleus of the hypothalamus in mature and old rats. It was established that daily fluctuations in the density of the studied structures are subject to circadian rhythms, with the highest values at 2 a.m., while at 2 p.m. it decreases. In old rats, the density of melatonin type 1A receptors in neurons of the anterolateral preoptic nucleus of the hypothalamus is lower than in mature rats. Light stimulation leads to desynchronization and decreased density of melatonin 1A receptors in both mature and aged rats. When using exogenous melatonin in the dose of 0.5 mg/kg against the background of long-term lighting, a probable increase in the mean density of melatonin 1A receptors in neurons of the anterior-lateral preoptic nucleus of the hypothalamus was observed.
Keywords: sleep-wake cycle; anterolateral preoptic nucleus of the hypothalamus; chronorhythms; lighting; melatonin